VALIDITY AND PRACTICALITY OF ENGINEERING DESIGN THINKING-BASED STUDENT WORKSHEETS: Bengkulu, Indonesia - Sukma Lestari; Masri; Risnanosanti (Jurnal Math-UMB.EDU, 2026)
This study aims to determine the validity and practicality of Engineering Design Thinking (EDT)-based Student Worksheets (LKPD). The research employed a development research method using three of the four stages in the 4D (Four-D) development model, namely define, design, and develop. The research subjects consisted of one teacher and 29 students in the implementation class. The instruments used included expert validation sheets and practicality questionnaires. The results showed that the validity score of the LKPD reached 88.61%, which falls into the "very valid" category. The practicality score based on the teacher's assessment averaged 87.5%, while the students assessment averaged 85.3%, indicating a high level of practicality. Therefore, it can be concluded that the developed Engineering Design Thinking-based LKPD meets the criteria of being valid and practical for use in the learning process. Keywords: Student Worksheets (LKPD), Engineering Design Thinking (EDT), Validity, Practicality.